Variation in Seedling Characteristics among Five Seed Sources of Teak (Tectona grandis L.f) in Kerala - Gunaga, Rajesh P.; Prabhu, H. Nagesh; Surendra, T. (Indian Forester, 2010)
Variation for seedling performance was investigated among five broad seed sources of teak (Tectona grandis Linn. f). Significant seed source variation was established for seedling characteristics of heiHht (9.56-16.82cm), basal diameter (2.68-4.40 cm), root biomass (0.51-2.33 g), leaf area (21.49-283.68 cm ), sturdiness quotient (0.28-4.37) and quality index (0.36-1.04). The present study indicated that seed sources such as Parambikulam, Nilambur and Konni performed better for seedling attributes. Correlation analysis indicated that seedling diameter was positively correlated with seedling height and total biomass of seedling, while shoot-root ratio was negatively correlated with total biomass of seedling and quality index, which indicates that an optimal S:R ratio would substantially increase seedling quality and vigour. Cluster analysis was done to assess phenotypic relationships among the seed sources and the dendrogram revealed three major clusters grouped according to rainfall distribution and altitude.